The Impact of Zakat Funds' Raising, Distribution, And Use On Mustahiq Welfare (Case Study BAZNAS Lumajang Regency) - Syarifah Aini (Muhasabatuna : Jurnal Akuntansi Syariah, 2022)
Islam is a true religion in which all facets of daily life are governed by it. Islam rules its people in many ways, and sharia is one of its main tenets. Islam therefore pays attention to economic issues because they can either make people more rich or more wretched. In order to attain the necessary sustainability, Islamic economics also needs respect for each person's rights as well as the rights of society at large. Zakat management, which is governed in Indonesia by Law Number 23 of 2011 concerning the management of zakat, is one of the methods currently used in Islamic economics to achieve the desired sustainability. According to this law, zakat management is the planning, implementation, and coordination of the collection, distribution, and use of zakat. The Amil Zakat Agency (BAZ) and the Amil Zakat Institution are the two different types of zakat administration entities in Indonesia, according to Law No. 23 of 2011. (LAZ). By examining meaningful or unmeaningful statics, this quantitative study seeks to determine if the theory that has been in force up to this point is true or untrue. Explanatory research, also known as research that explains relationships between variables in a study and tests hypotheses developed in light of theoretical studies. From the results of the analysis it was found thatvariableX_1there is a significant effect of collecting zakat funds on mustahiq welfare, namely with a significant value of 0.00 <0.05,variable X_2 there is a significant influence between the distribution of zakat funds on the welfare of mustahiq with a value of 0.03 <0.05,variableX_3 there is a significant influence between the utilization of zakat funds on the welfare of mustahiq with a significant value of 0.00 <0.05. Mean while simultaneously variable collection (fundraising), distribution, and utilization of zakat funds have a simultaneous effect on the welfare of mustahiq with a significant value of 0.00<0.05 And〖 F〗_(hitung )(18.8480)> F_tabel(2.69) so〖 H〗_aaccepted.